2017
DOI: 10.1111/jdi.12609
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis B virus infection status is more prevalent in patients with type 2 diabetes

Abstract: Aims/IntroductionIt has not been reported whether chronic hepatitis B virus infection (CHB) is associated with a specific type of diabetes. We sought to investigate the prevalence of CHB status in different diabetes subtypes among a Chinese population.Materials and MethodsThis was a cross‐sectional study. A total of 381 patients with adult‐onset autoimmune diabetes, 1,365 patients with type 2 diabetes and 1,365 non‐diabetic controls were recruited from June 2005 to February 2014. The exclusion criteria include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
0
17
3
1
Order By: Relevance
“…Therefore, the risk of HBV infection in the former group was 1.5 times higher than the latter group (18). Some studies have also confirmed the higher prevalence of DM among diabetic patients.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, the risk of HBV infection in the former group was 1.5 times higher than the latter group (18). Some studies have also confirmed the higher prevalence of DM among diabetic patients.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies on patients with hepatitis have also shown significant differences between diabetic and nondiabetic individuals regarding the mean ALT level (18,21), mean age, cirrhosis (23), mean BMI, AST, ALT, HbA1c, cholesterol, and triglyceride (24). Another study on patients with HBV showed that diabetic patients had a significantly higher mean age (47.4 vs. 57 years) and BMI (28.4 vs. 34.5 kg/m 2 ), compared to nondiabetic individuals (25).…”
Section: Discussionmentioning
confidence: 99%
“…IR is regarded as the main cause for MS and FL development and characterized by hindered insulin-mediated glucose utilization in target tissues. More studies show that IR and its related diabetes are more prevalent in chronic HBV infection [17][18][19][20]. This study's goal was to compare FBG levels and the development of FL between the control group and the CAHB group, in terms of IR.…”
Section: Discussionmentioning
confidence: 99%
“…For exogenous antibodies, hepatitis B surface antigen positivity during pregnancy has a moderate effect on an increased risk of GDM . Moreover, the pathophysiological mechanism by which HBV (hepatitis B virus) infection causes diabetes is characterized as a metabolic disorder due to decreased liver function . GDM has been reported to be related to the upregulation of circulating inflammatory factors .…”
Section: Discussionmentioning
confidence: 99%